The wife between us [large type] - Hendricks, Greer; Pekkanen, Sarah (Thorndike Press, a part of Gale, a Cengage Company, 2018)
When you read this book, you will make many assumptions. You will assume you are reading about a jealous wife. You will assume she is obsessed with her replacement - a woman who is about to enter a new marriage with the man she loves. You will assume you know the anatomy of the relationships. Assume nothing. Read between the lies. Twisted and deliciously chilling, The Wife Between Us deftly explores the hidden complexities of marriage and the dangerous truths we ignore in the name of love.